Transformasi Manajemen Pendidikan Islam di Abad ke-21 - Moh. Ersat; Laila Badriyah; Yuliastutik (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
Global changes marked by the rapid development of digital technology and social dynamics in the 21st century have brought major implications for education systems, including Islamic education. Islamic educational institutions face dual challenges, namely the demand to improve quality and competitiveness at the global level and the obligation to maintain Islamic values and identity. This condition requires a transformation of Islamic education management that is able to respond to changes in an adaptive and sustainable manner. This article aims to examine the transformation of Islamic education management in the 21st century by highlighting the paradigm shift in management, the role of transformative leadership, the use of digital technology, and the implementation of quality management. This research uses a qualitative approach through literature review of various relevant scientific sources. The results of the study show that the transformation of Islamic education management is a fundamental element in improving the effectiveness of the management of educational institutions. The integration between modern management principles and Islamic values is key in creating Islamic education that is relevant, quality, and able to produce intellectual, spiritual, and social superior human resources in the 21st century.